Reportagem “Bauru com limites: um olhar sobre a divisão social do município” - Assis, Felipe Sena de [UNESP]; Souza, Giovana Amorim de [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
O presente trabalho consiste no relatório final de um Trabalho de Conclusão de Curso cujo produto é uma reportagem opinativa. O projeto aborda a construção e o desenvolvimento da cidade de Bauru a partir da distribuição desigual de investimento público, da apropriação do espaço urbano pelos interesses privados e da segregação à população de bairros negligenciados pelo Estado. Para compor o material, a reportagem se pautou nas falas de moradores da cidade, especialistas em planejamento urbano e nas observações dos próprios autores.

The present work consists of the final report of a Course Completion Work whose product is an opinion report. The project addresses the construction and development of the city of Bauru from the unequal distribution of public investment, the appropriation of urban space by private interests and the segregation of the population from neighborhoods neglected by the State. To compose the material, the report was based on the speeches of city residents, specialists in urban planning and on the observations of the authors themselves
Report “Bauru with limits: a look at the social division of the county”
Keywords: Reportagem; Jornalismo opinativo; Planejamento urbano; Divisão social; News report; Opinative article; Urban planning; Social division